(untitled) (Prithvi Academic Journal, 2019)
The climate pattern of Nepal is uncertain regarding the precipitation but the extreme events such as floods and drought are increasing. Due to an increase in uncertain precipitation, the extreme rainfall and its intensity are also increased. Baglung District elevated from 650m to 4300m has a diverse climatic zone from upper tropical to alpine, almost similar to the whole Nepal. The data were taken from the Department of Hydrology and Meteorology from 1970 to 2018 (on monthly basis) are used for analyzing the precipitation trends in Baglung District based on five stations by taking the secondary data. To analyze the data, Mann- Kendall, and Sen’s Slope are used to find trend and magnitude. SPSS and R softwere are used to draw graph and other statistical calculations. The analysis shows that there is a positive trend in precipitation in the Baglung district. This is contradictory to national trends of precipitation, which is slightly negative. The maximum value of precipitation is 271.892mm in 1998, followed by 263.070mm in 2000, and the minimum value is 27.217mm in 1973, followed by 86.10 mm in 1972. There is a wide variation in average monthly rainfall in different stations ranging from 158.326mm (Baglung station) to 235.828mm (Rangkhani station) with standard deviations 199.342mm and 310.196mm respectively. The analysis indicates that the trend of precipitation is slightly positive but insignificant which shows that the intensity of rainfall is increased, but the number of rainy days is decreased. Similarly, the results indicate that the average rainfall in Baglung (190.400mm) is higher than the national level (150mm app.).